Kontroversi Putusan Mahkamah Konstitusi Membatalkan Kewenangan Komisi Yudisial Melakukan Rekrutmen Terhadap Hakim - Suparto, Suparto (SASI, 2020)
The Supreme Court conducted a selection of judges without the involvement of the Judiciary Committee. The Judiciary Committee deemed the recruitment was violating the law since it was not involving them in the process. While the Supreme Court viewed that the implementation guidelines for the mutual regulation of the Judiciary Committee and Supreme Court was yet to be existed, while the need for fresh judges was deemed as urgent at that time. Based on that premise, the Supreme Court conducted the recruitment and appointment of judges, several supreme court judges and registrars were conducting a judicial review on the Law No. 49 of 2009, Law No. 50 of 2009, and Law No. 51 of 2009.The Constitutional Court granted their plea with Stipulation No. 43/PUU-XIII/2015.One of the points of considerations of the constitutional judges was the involvement of Judiciary Committee on the recruitment of judges was deemed to disrupt the independency of the Supreme Court. Actually, the involvement of the Judiciary Committee in the selection of judges will not intrude the independency of the judicial power or the judge itself. The independency of judges will be disrupted if the Judiciary Committee is intervening with the technical aspect of judicial power which includescross-examination, trial, and the verdict on a case.